Studi Kasus Gangguan Kecemasan Umum Warga Binaan Wanita di Lapas Jakarta - Shofiyah Malik; Rilla Sovitriana (Jurnal Ilmiah Psikologi MIND SET, 2021)
Individuals who experience anxiety and worry when they are prisoners is normal, but if there is cognitive distortion and has been disturbing that eventually arises with physical complaints, it needs to be addressed. The subject of this study was a 39-year-old woman whose met the diagnostic criteria in the DSM-IV TR generalized anxiety disorder and is currently serving a prison term. Overcoming cases of generalized anxiety disorder, the subject was assisted by Rational Emotive Behavior Therapy (REBT) which was carried out for 10 sessions. This study uses a qualitative approach with case study methods, data analysis techniques using pattern matching and analysis of development results. The results of the measurement of anxiety using the Hamilton Anxiety Rating Scale (HARS) in the form of pre-test and post-test. The results of the pre-test showed in the category of moderate anxiety, based on the results of the application of Rational Emotive Behavior Therapy on the subject showing calmer, more peaceful behavior, more stable emotions, able to concentrate, able to sleep, and able to think rationally, these result are supported by the post test results which show a decrease in anxiety to a mild category